Model Sistem Informasi Manajemen Pabrik Roti Dengan Penerapan Enterprise Resource Planning - Mega Andriani; Triase Triase; Raissa Amanda Putri (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
The Sri Deli bakery business was founded in 2019 and is currently still recording income and expenses using Microsoft Excel application in a simple format. This causes errors in data recording and results in non-integration with ongoing business processes, and is not monitored in real-time. To control the risk of errors in recording stock, expense, income and employee data, Busrain Bakery requires a management information system that is integrated and monitored in real-time. The application of Enterprise Resource Planning in the Management Information System can help users of the Busrain Bakery Bread Factory record sales, purchases, stocks and payroll in more detail. The Laravel framework and MySQL database are used in the development of a management information system that can reduce fraud in financial and inventory management, as well as make it easier for factory leaders to access financial reports, employee data, and inventory.Keywords: Enterprise Resource Planning; Management Information System; Web; Laravel AbstrakUsaha roti Sri Deli berdiri sejak tahun 2019 dan saat ini masih melakukan pencatatan pendapatan dan pengeluaran dengan menggunakan aplikasi Microsoft Excel dalam format yang sederhana. Hal ini menyebabkan kesalahan pencatatan data dan mengakibatkan tidak terintegrasinya proses bisnis yang berjalan, serta tidak terpantau secara realtime. Untuk mengendalikan risiko kesalahan pencatatan persediaan, pengeluaran, pendapatan dan data karyawan, Busrain Bakery memerlukan sistem informasi manajemen yang terintegrasi dan termonitor secara real-time. Penerapan Enterprise Resource Planning pada Sistem Informasi Manajemen dapat membantu pengguna Pabrik Roti Busrain Bakery dalam mencatat penjualan, pembelian, persediaan dan penggajian dengan lebih detail. Framework Laravel dan database MySQL digunakan dalam pengembangan sistem informasi manajemen yang dapat mengurangi kecurangan dalam manajemen keuangan dan inventaris, serta memudahkan pimpinan pabrik untuk mengakses laporan keuangan, data karyawan, dan inventaris.